Demographical and clinicopathological characteristics in heart failure and outcome predictors: a prospective, observational study. (7th October 2016) - Sajeev, Chakanalil Govindan; Rajan Nair, Shreetal; George, Biju; Rajesh, Gopalan Nair; Krishnan, Mangalath Narayanan
Abstract: Aims: The aims of the study were to study the demographical and clinicopathological characteristics of patients presenting with heart failure and evaluate the 1 year outcomes and to identify risk predictors if any. Methods and results: A prospective observational study was conducted in consecutive patients of systolic heart failure. The study was divided into two parts—an initial 6 month enrolment phase followed up for 1 year for major adverse cardiovascular events. All patients were treated according to the Institutional Heart Failure Protocol. Demographical and clinicopathophysiological characteristics were studied, and results were analysed. A total of 143 patients were enrolled. The mean age of subjects was 56.4 years with male subjects constituting almost two‐thirds of the study population. The commonest aetiology of heart failure was ischemic with valvular heart disease being the commonest cause of non‐ischemic heart failure. Bendopnea, a recently described symptom of heart failure, was found in a significant number of subjects. By univariate analysis, male sex ( P  = 0.042) and cardiomegaly ( P  = 0.035) were predictors of rehospitalization, whereas the univariate predictors of mortality were ischemic aetiology ( P  = 0.000), age > 50 years ( P  = 0.007), hypertension ( P  = 0.012), worsening NYHA class ( P  = 0.003), diabetes mellitus ( P  = 0.009), and hypokalaemia ( P  = 0.006). Multivariate analysis performed showed age > 50 years [ P  = 0.007; OR (CI) = 13.547 (2.034–90.238)], NYHA class [ P  = 0.002; OR (CI) = 32.300 (3.733–276.532)], and hypokalaemia [ P  = 0.031; OR (CI) = 7.524 (1.208–46.862)] as significant predictors of mortality during long‐term follow‐up. Conclusions: The study will definitely help us to throw more light in identifying risk predictors of heart failure and help in improving clinical outcomes.